Organizational Learning in a High-Risk Environment: Responding to an Anthrax Outbreak - Shari R. Veil; Timothy L. Sellnow (Journal of Applied Communications, 2008)
The National Center for Food Protection and Defense, a Department of Homeland Security-sponsored Center of Excellence, identified and endorses 10 best practices for risk and crisis communication. The best practices model is designed to aid organizations of all types in preparing for and learning from crisis events. This analysis applied the best practices model to a case study of an anthrax outbreak that fostered a full-blown crisis response. This study analyzes the learning experience of the crisis cohort group that responded to the crisis. The researchers contend that by evaluating a crisis situation using best practices as a benchmarking procedure, problems within the system and new strategies can be identified.
Keywords: High-Risk; environment; Anthrax; Outbreak; benchmarking; procedures; problems